Pengaruh Kualitas Pelayanan Terhadap Kinerja Pegawai Dikantor Badan Pemeriksa Keuangan Perwakilan Provinsi Gorontalo - Kadir, Melisya; Igirisa, Irawaty; Nani, Yacob Noho (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Service quality greatly influences employee performance. The aim of this research is to find out how much influence service quality has on employee performance at the Gorontalo Province Representative Financial Audit Agency office. The researcher took the research location at the office of the Gorontalo Province Representative Financial Audit Agency with a sample size of 50 respondents. The research method used in this research is a quantitative method. Data collection techniques were obtained from the results of observations and distribution of questionnaires and using data analysis techniques using simple linear regression tests and coefficient of determination tests. From the results of data analysis in this study, it is stated that the respondents' responses regarding the service quality variable have an average of good alternative answer criteria. Meanwhile, the employee performance variable has an average alternative answer which is quite good. From the research results, it can be concluded that there is a positive and significant influence between service quality on employee performance at the Gorontalo Province Representative Financial Audit Agency office of 84.3% and the remaining 15.7% is influenced by other variables not examined in this research               .